A Holistic approach to corporate sustainability assessment: Incorporating sustainable development goals into sustainable manufacturing performance evaluation. (January 2019) - Moldavska, Anastasiia; Welo, Torgeir
Highlights: Corporate sustainability assessment (CSA) in manufacturing has a variety of challenges. Viewing sustainability as a process of directed change or transition can address the weaknesses of CSA. Systems representation of manufacturing company is crucial in assessing sustainability performance of a company. CSA that links organizational model and sustainability criteria can aid the decision-making. Abstract: Corporate Sustainability Assessment (CSA) in manufacturing is a framing of tools that guide the organization toward sustainable practices and indicate how the same organization contributes to a global Sustainable Development (SD). In addition to the discussion about shortcomings of existing CSA practices, the need to incorporate UN Sustainable Development Goals (SDGs) into reporting has been advocated by the sustainability society. This paper proposes a new CSA method for manufacturing companies in which (1) sustainability is seen as a process of directed change, (2) assessment tool is designed by modeling manufacturing company using systems representation, and (3) assessment of Corporate Sustainability (CS) is context-based and linked to SDGs. The proposed CSA method takes a holistic view on Sustainable Manufacturing (SM) and CS.